PENGEMBANGAN MEDIA BIANKA (BIANGLALA PECAHAN MATEMATIKA) MENGGUNAKAN PENDEKATAN KONTEKSTUAL BERBASIS LITERASI MATEMATIS PADA SISWA KELAS IV SEKOLAH DASAR - Kifayah, Riza Fatimatul; Kusuma, Dani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by students' lack of understanding of fractions and limited mathematics learning media in schools. This is one of the factors in students' lack of motivation and enthusiasm for learning. The development of BIANKA (Mathematical Fraction Ferris Wheel) media is one solution to overcome this problem. This research was conducted at SDN Blotongan 02 Salatiga. This research uses the Research & Development (R&D) method with the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The method used in this research is quantitative descriptive. The data collection techniques used are observation, interviews, response questionnaires, tests, validation sheet instrument assessments, practicality and effectiveness. The media validation results were 96% in the